Developing Artificial Neural Network Based on Visual Studio for Dance Assessment - Rahmahwati, Febri Suci; Arifin, Fatchul (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
The dance assessment test still uses a manual system that tend to have frequent errors in the calculation for the final results thus it requires a system that accelerate the assessment process with an accurate result. This study aimed at: (1) designing an artificial neural network application based on visual studio for the dance assessment. (2) examining the performance of the artificial neural network application based on visual studio for the dance assessment. The design method consists of (1) system design (2) interface design (3) database design for artificial neural network system. (4) design of artificial neural network model. (5) programming (6) system testing. The design of visual studio artificial neural network application for the dance assessment has two stages: main program and supporting program. This research built a system by implementing visual studio and artificial neural network to assess dance examination which can give the final result to each participant directly. The application of the dance assessment can assess 3 types of dance with a training set of at least 10 pairs to undertake learning that produces the load to be used in the assessment. Besides assessing, this application can also delete, repair, and store data in the form of .xls. Based on the test results, it can be concluded that the application operates effectively for determining the final load, data input and data storage.